2002
DOI: 10.1081/jdi-120004094
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy Is a Risk Factor Independent of Hypertension in Survival of Hemodialyzed Patients

Abstract: Hemodialysis patients have low 5-year survival rates of approximately 60%, and the most common cause of death is cardiovascular diseases. Their population may be considered, therefore, as an accelerated model in analyzing the risk factors for cardiovascular diseases. We previously reported the role of blood pressure, one of the most important risk factors for cardiovascular diseases, in determining the prognosis of hemodialysis patients. In this study, we examined the effect of cardiomegaly detected on chest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
2
7
2
Order By: Relevance
“…With respect to total mortality and CVE, we found a significant association in the univariate, but not in the multivariate, analyses. This is partly consistent with earlier findings but does not comply with data mainly derived from echocardiographic studies showing a clear association between LVH and mortality in hemodialysis populations (19)(20)(21)(22)(23). This might be due to the fact that the sensitivity of hypertrophy markers in the ECG is low (24,25).…”
Section: Discussionsupporting
confidence: 77%
“…With respect to total mortality and CVE, we found a significant association in the univariate, but not in the multivariate, analyses. This is partly consistent with earlier findings but does not comply with data mainly derived from echocardiographic studies showing a clear association between LVH and mortality in hemodialysis populations (19)(20)(21)(22)(23). This might be due to the fact that the sensitivity of hypertrophy markers in the ECG is low (24,25).…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, other studies that have reported LVH as a prognostic marker had a prevalence of LVH ranging from 65% to 75% [6][7][8]10]. The relative risk of CVE in this analysis was more than 60% higher for patients with the largest LVMI (>180) as compared with those who had a lesser degree of LVH.…”
Section: Comparison Of Findings With Other Published Reportscontrasting
confidence: 51%
“…These studies differ from FOSIDIAL in that the timing of LV mass measurement was remote from study enrolment (1 year) [6], whereas LV mass was measured within 3 months of randomization in the FOSIDIAL study. Other studies measured LVH by electrocardiogram [8]. These factors and other differences in study populations may account for the greater risk associated with LV mass in our study.…”
Section: Comparison Of Findings With Other Published Reportscontrasting
confidence: 37%
See 2 more Smart Citations